Method for preparing methyl alcohol, formaldehyde and CO used for methane direct selective oxidation - WANG SHUAI; ZHANG ZHAOXIA; TIAN JINSHU; TAN JIANGQIAO; LIN JINGDONG; WANG YONG (2018)
The invention discloses a method for preparing methyl alcohol, formaldehyde and CO used for methane direct selective oxidation. The method comprises the following steps: preparing a BN powder materialcatalyst, after mixing boric acid with urea, dissolving and stirring with a water and methyl alcohol mixed solvent, carrying out thermostatic waterbath standing for crystallization, and roasting under an inert atmosphere to obtain a BN powder material; tabletting and forming a roasted sample, smashing and sieving to obtain a BN powder material catalyst; catalyst activation: introducing oxygen-containing gas into a continuous flow reactor filled with the BN powder material catalyst for heating, activating, introducing inert gas, adjusting to a reaction temperature, and switching into a reaction gas; and preparing methyl alcohol, formaldehyde and CO. 种用于甲烷直接选择氧化制备甲醇、甲醛、CO的方法，涉及甲烷。制备BN粉末材料催化剂，将硼酸和尿素混合后，用水和甲醇混合溶剂溶解、搅拌后，恒温水浴静置进行晶化，在惰性气氛下焙烧，得BN粉末材料；将焙烧样品压片成型，粉碎，过筛，得BN粉末材料催化剂；催化剂活化：将含氧气体通入装有BN粉末材料催化剂的连续流动反应器中加热，活化，通入惰性气